Farmer Producer Organization – A new initiative to augment farmer’s income - Kaur Mavi, Harsimranjeet; Mamgai, Preeti; Singh Brar, Amandeep (Indian Farming, 2022)
The farmers who are active members and shareholder of the FPO are more gratified by marketing their produce to the final consumer and gaining more profit by saving the commission at different levels which was earlier given to the middlemen. Processing and value addition helps in enhancing the income of farmers that they generate earlier from traditional agricultural crops. This is a good beginning and we can anticipate the FPO to attain more success in future.